Optimization of Bacterial Cellulose Production from Pineapple Waste: Effect of Temperature, pH and Concentration - Junaidi, Zakaria; Muhammad Azlan, Nazeri (2012)

(untitled)
Bacterial cellulose is a type of biopolymer produced by Acetobacter xylinum in high purity, high water holding capacity, good mechanical strength, elasticity and high crystallinity. In this research, pineapple waste is used as the carbon sources for the synthesis of bacterial cellulose. The objective of this study is to investigate the effect of temperature, pH and concentration of pineapple waste in the production of bacterial cellulose by Acetobacter xylinum. Parameters investigated are varied from 40% to 100% for the concentration, while the temperature is between 28°C to 32°C and pH of 4.5 to 8.5. Besides, this study also aims to optimize the production of bacterial cellulose from pineapple waste by using response surface methodology (RSM) based on the central composite design (CCD). The known value of the parameters is estimated earlier based on one factor at that time (OFAT). The results obtained from the OFAT showed the optimum condition is at pH 5.50, temperature 30°C and concentration of pineapple waste is 80 %, where the amount of bacterial cellulose dry weight is 3.3948g. According to the RSM result, the optimal conditions for bacterial cellulose were pH 5.15, temperature 30.51°C and concentration of pineapple waste is 83.32%. By using these optimal conditions, 3.4368g of bacterial cellulose is produced. The existence of bacterial cellulose is proven by Fourier Transform Infrared (FT-IR) Spectroscopy analysis based on the appearance of absorbance peak which are C-C bonding, C-O bonding, C-OH bonding and C-O-C bonding. In short, the data presented in this paper showed that pineapple waste has a great potential to use as the carbon source in production of bacterial cellulose